ILO Global Estimates on International Migrant Workers Results and Methodology. Third Edition. - Office, International Labour (International Labour Organisation (ILO), 2021)
This report's third edition presents the most recent estimates on the stock of international migrant workers, disaggregated by age, sex, country-income group and region, and the estimation methodology. The reference year is 2019. The estimates offer a benchmark against which the COVID-19 driven changes can be analysed in the future.